Myosin-cross-reactive epitope of Shigella flexneri invasion plasmid antigen B. - Oaks, E V (1992)
IpaB, invasion plasmid antigen B, of Shigella flexneri is a 62-kDa protein required for invasion of intestinal epithelial cells. IpaB is also one of several major protein antigens recognized by the humoral immune systems of most humans and monkeys after infection with shigellae. Computer analysis of the deduced IpaB amino acid sequence indicates that an alpha-helical structure is likely through much of the molecule. Homology searches with protein data banks show that one alpha-helical domain between amino acid residues 95 and 181 has a moderate level of identity with myosin and streptococcal M protein. By using a monoclonal antibody (2F1) which recognizes an epitope in the amino-terminal third of the IpaB protein, it was possible to demonstrate a cross-reactive epitope(s) on skeletal muscle myosin. Epitope mapping localized the 2F1 epitope to three noncontiguous regions of the IpaB protein within the alpha-helical domain that contains homology with myosin. Antibodies produced in rabbits immunized with synthetic peptides from one of the 2F1 epitope regions (residues 99 to 110) of IpaB were capable of reacting with IpaB as well as myosin. Furthermore, sera from several monkeys previously infected with S. flexneri 2a contained antibodies to IpaB pep 101-116 (IpaB peptide 101-116) and also myosin. Sera from animals with antibodies against other IpaB peptides did not contain antibodies against myosin.